DISTRIBUTION OF MYCOPLASMA SPP. AND UREAPLASMA SPP. AMONG PREGNANT WOMEN - Anton G. Petrov; Vladislav M. Nankov; Rositsa V. Petrova; Irena I. Gencheva; Milena D. Karcheva (Peytchinski Publishing, 2021)
The purpose of the present study is to determine the prevalence of genital mycoplasmas (M. genitalium, M. hominis, U. parvum, U. urealyticum) in pregnant women by molecular biological methods. Material/Methods: A prospective epidemiological study of 107 pregnant women hospitalized in the Clinic of Obstetrics and Gynecology, University Hospital-Pleven, Bulgaria, was conducted. Vaginal secretion samples were taken from all 107 pregnant women. A Polymerase chain reaction (PCR) assay was used to detect the genomic DNA of the bacteria in pregnant women. Results: The highest is the relative share of women in the age group from 20 to 35 years - 66 (64.68%), followed by women under 20 years - 27 (25.23%) and women over 35 years - 14 (13.08%). Detection of bacterial DNA was found in 85 (79.44%) of the cases, with present Ureaplasma spp. Colonization in 42 women (39.25%). Although no statistical dependence was found on open bacteria and age groups (p-value = 0.4688), it is noteworthy that the prevalence of Mycoplasma spp. and Ureaplasma spp. as a whole in the age group from 20 to 35 years, which has the highest birth rate, is more than twice higher than the group of up to 20 years and more than five times higher compared to the group over 35 years. Conclusions: Studies on the incidence of Mycoplasma spp. and Ureaplasma spp. in pregnant women is important for controlling the pregnancy, predicting the risk of developing maternal-fetal infection and discussing the options for timely treatment.